2014
DOI: 10.1177/0268355512471757
|View full text |Cite
|
Sign up to set email alerts
|

The use of ultrasound in the evaluation of the efficacy of calf muscle pump function in primary chronic venous disease

Abstract: Patients with moderate CVD have lower FV during calf muscles contraction but similar muscle anatomical characteristics compared with healthy controls. Changes in calf muscles flexibility and fatigue resistance may be investigated as possible causes of calf pump dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
2
8
3
1
Order By: Relevance
“…The increase in blood flow velocity in the superficial GSV during active and passive movements of ankle is also similar to that observed here using call-up and reabsorption maneuvers. 36 In the standing position and during active tip-toe movements, blood flow velocity in the popliteal vein also increases in response to calf muscle pump contractions, 28 but in this case and contrary to what was observed in the present study, healthy subjects demonstrated larger enhancement in venous blood flow as a result of the tip-toe movement. 28 There are few studies that describe and demonstrate the efficacy of MLD maneuvers on venous blood flow.…”
contrasting
confidence: 94%
“…The increase in blood flow velocity in the superficial GSV during active and passive movements of ankle is also similar to that observed here using call-up and reabsorption maneuvers. 36 In the standing position and during active tip-toe movements, blood flow velocity in the popliteal vein also increases in response to calf muscle pump contractions, 28 but in this case and contrary to what was observed in the present study, healthy subjects demonstrated larger enhancement in venous blood flow as a result of the tip-toe movement. 28 There are few studies that describe and demonstrate the efficacy of MLD maneuvers on venous blood flow.…”
contrasting
confidence: 94%
“…Such apparent calf pump dysfunction might be related to weak calf muscles in CVD patients [29,30] and is compatible with a lower ejection volume, such as has been measured before in this population with air-plethysmography [92]. In addition, abnormal venous blood reflux from deep to superficial venous system through incompetent perforator veins may blunt blood flow through the popliteal vein [104].…”
Section: Impairment Of Calf Muscle Pump and Functional Capacitymentioning
confidence: 54%
“…Popliteal peak flow volume is maximal during the first contraction of the tip-toe set of ten repetitions when the venous reservoir is full [103]. In the CVD patients, but not in the healthy subjects, venous flow augmentation was seen to diminish during the ten tip-toe exercise [104]. Such apparent calf pump dysfunction might be related to weak calf muscles in CVD patients [29,30] and is compatible with a lower ejection volume, such as has been measured before in this population with air-plethysmography [92].…”
Section: Impairment Of Calf Muscle Pump and Functional Capacitymentioning
confidence: 90%
See 2 more Smart Citations